2004
DOI: 10.1002/cfg.406
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and cellular function of monothiol glutaredoxins: involvement in iron–sulphur cluster assembly

Abstract: A number of bacterial species, mostly proteobacteria, possess monothiol glutaredoxins homologous to the Saccharomyces cerevisiae mitochondrial protein Grx5, which is involved in iron-sulphur cluster synthesis. Phylogenetic profiling is used to predict that bacterial monothiol glutaredoxins also participate in the iron-sulphur cluster (ISC) assembly machinery, because their phylogenetic profiles are similar to the profiles of the bacterial homologues of yeast ISC proteins. High evolutionary cooccurrence is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 68 publications
0
61
0
Order By: Relevance
“…This induced substantial and efficient cable formation in both cells growing exponentially and in response to treatment with the oxidant hydrogen peroxide, as is clearly shown and quantified in Fig. 7C and D. Both Trx domains contain a WAD/EPCK sequence that is reminiscent of the authentic active site motif of thioredoxins WCGPCK (45). We therefore raised the question as to whether the function that both Trx domains demonstrate in actin cytoskeleton polarization could have been exerted through the cysteine residues contained in their putative active site motives.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…This induced substantial and efficient cable formation in both cells growing exponentially and in response to treatment with the oxidant hydrogen peroxide, as is clearly shown and quantified in Fig. 7C and D. Both Trx domains contain a WAD/EPCK sequence that is reminiscent of the authentic active site motif of thioredoxins WCGPCK (45). We therefore raised the question as to whether the function that both Trx domains demonstrate in actin cytoskeleton polarization could have been exerted through the cysteine residues contained in their putative active site motives.…”
mentioning
confidence: 55%
“…We have also demonstrated that the role that both Grx3 and Grx4 play in actin cable formation is not the consequence of the intracellular accumulation of iron described in the grx3 grx4 double mutant (39), or of ROS accumulation, which was determined in the absence of Grx3 and Grx4 in this study. Each of the two Grx3 and Grx4 proteins has one thioredoxin domain (Trx), followed by one glutaredoxin domain (Grx) (5,39,45). In a previous study, we demonstrated that each Grx domain of both Grx3 and Grx4 played a role in Aft1 translocation from the nucleus to the cytoplasm.…”
Section: Discussionmentioning
confidence: 98%
“…The vector pTP19 bears the Grx domain of Grx4 constructed in pGBT9 in EcoRI-PstI sites by using GSLOL52 and MMO171. As a control for positive nuclear interaction we used the pair of plasmids pACT2SNF4 and pGBT9SNF1 (see Vilella et al, 2004). And finally pACT2YAK1 and pGBT9GRX5 were used as a negative control for nuclear interaction (Vilella et al, 2004).…”
Section: Dna Manipulation and Plasmidsmentioning
confidence: 99%
“…As a control for positive nuclear interaction we used the pair of plasmids pACT2SNF4 and pGBT9SNF1 (see Vilella et al, 2004). And finally pACT2YAK1 and pGBT9GRX5 were used as a negative control for nuclear interaction (Vilella et al, 2004). The plasmid pMM351 is an integrative vector that contains three repetitions of the hemagglutinin (HA) epitope in the C-terminal position and also bears the regulatable tetO 7 promoter.…”
Section: Dna Manipulation and Plasmidsmentioning
confidence: 99%
“…Instead, the capability to coordinate ISCs appears to be a common feature for 1-C-Grxs (16,40,42,43,54,67,89) with yeast Grx7 being, so far, the only known exception (59,60). The latter feature determines an evolutionary conserved and indispensable role of 1-C-Grxs in the biogenesis and assembly of iron-sulfur proteins (11,61) and other cell-specific regulatory functions such as the (in)activation of nuclear transcription factors (35,62,86).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%